(untitled) (Global Journal of Science Frontier Research, 2025)
According to the energy conservation equation, two novel conservative numerical methods are proposed for solving the second-order initial value problems. The -continuous piecewise-quadratic functions are also used to approximate the true solutions. A priori error estimate is derived under a linear force assumption of the initial value problems. Some numerical tests are conducted to verify the theoretical results.